Accuracy Analysis of Terrestrial Data Transformation from Bessel Datum for Precision Well-Head Mapping - Nuriyanto; Mohamad Abdul Basyid (Faculty of Engineering, Universitas Serambi Mekkah, 2026)
The use of local Bessel 1841 datum in historical terrestrial datasets within the oil and gas sector presents challenges for integration with the modern WGS84/SRGI2013 reference system. This study aims to evaluate the positional accuracy of terrestrial data based on Bessel 1841 Datum in representing well-head locations in Sukowati Field after transformation to WGS84/SRGI2013 using 2D Helmert Transformation. The dataset consisted of 41 well-head points grouped into two clusters, namely SP.A and SP.B, with GNSS survey data collected in 2023 used as the references. Transformation parameters were estimated using the Least Squares method with a centroid approach to improve numerical stability. The results revealed a systematic shift between the two datums of approximately +105 m in the Easting direction and −41 m in the Northing direction. Accuracy assessment showed total RMSE values of 0.273 m for Cluster SP.A and 0.328 m for Cluster SP.B. These results indicate that the transformed coordinates achieve decimeter-level accuracy and remain below the 0.5 m tolerance threshold. Therefore, historical datasets based on Bessel 1841 Datum can still be reliably utilized after transformation to WGS84/SRGI2013 to support mapping activities and asset management in the oil and gas industry requiring high positional accuracy.